Rural Urban Classification (RUC) and its impact on funding pattern for urban development in the context of Indian cities - Dutta, Sourovee; Roy, Madhumita (International Journal of Engineering and Technology, 2018)
This paper attempts to assess the impact of existing Rural-Urban Classification (RUC) on distribution of development funds among different realms of a settlement in Indian context. The paper questions upon the existing parameters of Census definitions for ‘Urban’ and ‘Rural’ and how it is affecting the ‘Master Plan Preparation Process’ for cities. Further, it indicates the role of RUC for creating disparity in distribution of various Government development funds among settlements, by discussing ten diverse contexts of the country. Due to census definition of settlement classification in a dichotomous fashion, all these developmental schemes are being applicable to Statutory Towns only, the Census Towns are completely ignored, especially the peripheral settlements around major urban centers. The paper seeks to analyze the interrelationship between present funding pattern and degree of urbanization in the selected cases, if exists at all. The paper concludes with a framework to establish a relationship between funding pattern and urbanization and develops an approach towards restructuring the settlement classification, where in the future, the Peri-Urban realms / Census Towns can be considered under urban development schemes, can undergo planned urbanization and as a result, disparity in terms of development can be minimized in the country.